A New Nelala (Odonata: Frenguelliidae) from the Eocene of Arroyo Chacay, Patagonia, Argentina - Petrulevicius, Julian Fernando (2023)
A new species of Odonata, Nelala chacay sp. nov., from the Eocene of Northern Patagonia, Argentina, is described. The new species is the sixth one of the endemic Patagonian Eocene family Frenguelliidae. Nelala chacay sp. nov. is characterized mainly by the five postdiscoidal cells between MA and MP, and a RP3+4 only two cells and a half basal to subnodus.